Development A New Costing Structure In Product And Service Operation Using Time Driven Activity based Costing - Sri Nur Areena, Mohd Zaini; Mohd Yazid, Abu (Universiti Utara Malaysia, 2022)
In current practice of costing method in palm oil plantation, the method does not implement time equation so processing time determined by company is not in accordance with actual processing time in work station. Then, the present implementation in academic library do not illustrate the correlation between supplied resources and practical capacity. It is to develop capacity cost rate in order to interpret it in form of unused capacity. The purpose of this study is to build a new costing structure in product and service operation using time driven activity-based costing (TDABC). For product operation, this work carried on at a palm oil plantation in Prosper Palm Oil Mill Sdn. Bhd., Pahang. For service operation, data collection of academic library is taken in Universiti Malaysia Pahang. Eventually, in product operation, the total used time in all three activity centers of palm oil plantation are 3,220,928.04 minutes for mature area and 2,390,513.94 minutes for immature area. On the other hand, in service operation, the unused capacity is RM40,960.02 and RM144,202.51 in local and oversea material respectively. In terms of unused capacity, there are no significant differences when applying TDABC in product and service operation. Whereas, regarding of process dependency, activities in product operation are dependent to one another.